(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The new species Tuberculatus (Tuberculoides) inferus sp. n. is described from Sicily, Italy, where it lives on Quercus pubescens Willd. Short notes are given on the morphology of the alate viviparous female, the alatoid nymph and embryo; the taxonomic position of the new taxon is also discussed and information is given on its distribution and ecology.